2014
DOI: 10.1063/1.4861797
|View full text |Cite
|
Sign up to set email alerts
|

Observation of strontium segregation in LaAlO3/SrTiO3 and NdGaO3/SrTiO3 oxide heterostructures by X-ray photoemission spectroscopy

Abstract: LaAlO3 and NdGaO3 thin films of different thicknesses have been grown by pulsed laser deposition on TiO2-terminated SrTiO3 single crystals and investigated by soft X-ray photoemission spectroscopy. The surface sensitivity of the measurements has been tuned by varying photon energy hν and emission angle Θ. In contrast to the core levels of the other elements, the Sr 3d line shows an unexpected splitting for higher surface sensitivity, signaling the presence of a second strontium component. From our quantitative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
4
8
0
Order By: Relevance
“…The grey component is thus attributed to Ti atoms in a TiO 2 environment, and labelled Ti-TiO 2 in the following. Similarly, the chemical shift between the blue and pink components in the Sr3d core levels of samples A, B and E is 1.24 eV, in the same range as that reported for the chemical shift between Sr in a SrO environment and Sr in a STO environment (in the 1-1.2eV range 21,22,23 ). This component, labelled Sr-SrO in the following, is thus attributed to Sr atoms in a SrO environment.…”
Section: Figure 1 : Stem Images Of Samples C D E and Hsupporting
confidence: 81%
“…The grey component is thus attributed to Ti atoms in a TiO 2 environment, and labelled Ti-TiO 2 in the following. Similarly, the chemical shift between the blue and pink components in the Sr3d core levels of samples A, B and E is 1.24 eV, in the same range as that reported for the chemical shift between Sr in a SrO environment and Sr in a STO environment (in the 1-1.2eV range 21,22,23 ). This component, labelled Sr-SrO in the following, is thus attributed to Sr atoms in a SrO environment.…”
Section: Figure 1 : Stem Images Of Samples C D E and Hsupporting
confidence: 81%
“…The clear defect candidate for this is a strontium vacancy V 00 Sr . As reported in the literature [18,20,21,32,80], these are readily induced at oxide interfaces during growth and annealing procedures [24], such as indicated, e.g., by observation of SrO segregation during growth of LAO (and NGO) [34]. The Schottky equilibrium is active during the PLD growth process [21,54,80], so that the variation of the p dep affects the strontium vacancy concentration present at the NGO/STO interface.…”
Section: ••mentioning
confidence: 78%
“…Sharing a similar ionic structure with LAO (A 3þ B 3þ O 3 ), NGO generally causes a similar interface reconstruction as LAO when grown on f100g STO [32][33][34]. However, NGO possesses Nd 3þ ions carrying a magnetic moment that is not present in LAO.…”
Section: Introductionmentioning
confidence: 99%
“…A recent experiment revealed that, in the well-known (TiO 2 ) 0 /(LaO) 1+ LAO/STO HS system, the Sr atoms can even diffuse from the interface to the surface, forming SrO surface layer. [28] As discussed later, after structural relaxation, strong polarization may occur in the CZO/STO HS models. The periodic boundary condition in the supercell approach determines that there might exist an electric-field interaction between the surface of the STO substrate and the surface of the CZO film, though the strength strongly depends on the vacuum thickness.…”
Section: Structural Modeling and Computational Detailsmentioning
confidence: 91%